Arthropod Granivory of Lime-Coated Cover Crop Seeds. Issue 4 (27th May 2020) - Bredeson, Michael M; Beck, Dwayne; Lundgren, Jonathan G
Abstract: Diversifying cropland plant communities is prerequisite to restoring ecosystem functions in agricultural habitats. Cover crops are one such way to improve biodiversity, and broadcasting calcium carbonate-coated (lime) seeds can be a viable method for plant establishment. In addition to improving seed-to-soil contact, calcium carbonate may also reduce arthropod granivory. Here we examine the effect of this seed-coating technology on arthropod granivory for seven cover crop species under field conditions. Carabidae, Gryllidae, and Staphylinidae were the three most frequently collected granivorous taxa in pitfall samples, and Pterostichus permundus and Gryllus pennsylvanicus represented 60.8% of all individual granivores. Cover crop seed damaged was variable among plant species. Among all plant species, the presence of a seed coating significantly reduced granivory by nearly 40% in the 7-d field exposure. Individually, hairy vetch and sorghum × sudan seeds were especially protected by calcium carbonate. No positive correlations were observed between invertebrate groups and the number of seeds consumed. Alternative methods for assessing the functionality of granivorous arthropod communities should be pursued, as activity-density measured from pitfall traps failed to reveal important cover crop seed consumers. Protection of cover crop seeds from granivory through a calcium carbonate coating may allow producers to adjust seeding rates and save on costs, increasing the rate of adoption for this conservation practice.